Impact of an RN-led Medicare Annual Wellness Visit on Preventive Services in a Family Medicine Practice. (August 2021) - Farford, Bryan A.; Baggett, Christy L.; Paredes Molina, Carolina S.; Ball, Colleen T.; Dover, Carla M.
Objective: To evaluate the impact of a registered nurse (RN)-led Medicare annual wellness visit (AWV) on preventive services in a family medicine clinic. Patients and Methods: A retrospective chart review was performed on patients who underwent an RN-led AWV and patients who underwent a standard assessment (SA) between October 2017 and October 2018. A total of 630 patients (330 AWV and 300 SA) were included in this study. Results: There were seven preventive services examined for in women and five preventive services examined for in men. Each service was used more often by patients in the AWV group than the SA group (all odds ratios ≥1.64; all P values ≤.004). Conclusion: The RN-led AWV is an effective way to assist Medicare beneficiaries in meeting their preventive needs while allowing physicians more time to focus on chronic and acute needs.